PERSEPSI DAN MAKNA PERUBAHAN IKLIM TERHADAP USAHA PERTANIAN: STUDI KASUS DI DESA SUNGAI RANGAS TENGAH KABUPATEN BANJAR - Akhmad Rozami Syahru Alam; Mahrus Aryadi; Danang Biyatmoko; Trisnu Satriadi (EnviroScienteae, 2012)
This research was aimed to explore the society perception to climate change impacts which related to agricultural activities, rice productivity and farmers’ income; to do in-depth study about farmers’ definition related with climate change; and to absorb ideas and identification to agricultural alternatives. Survey method, interview and questionnaires were conducted to samples (respondent) which purposively chosen. This research was divided into three terms. At the first term, we use perceptional value test, chi square and contingentional coefficient. Second term, we applied the marker (sign) test. At the final term we applied focus group discussion technique. The result showed that: perception of farmer society was climate change have impacts to their agricultural activities, so that decrease rice productivity and income, but it have small effect to farmers’ innovation effort. Climate change was already realized by farmer society in Sungai Rangas Tengah Village Banjar Regency. Agricultural alternatives for farmer society to overcome these problems, were: poultries (42.65%), non-rice agriculture (26.47%), others (marketing, handcrafter, labor) (20.59%), fisheries (17.65%).